Investigation on Plasmodium falciparum and Plasmodium vivax Infection Influencing Host Haematological Factors in Tribal Dominant and Malaria Endemic Population of Jharkhand - Mohammad Raziuddin; Mohammad Mobassir Hussain; Mohammad Sohail; Kumar Abhishek (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
The study was undertaken to elucidate the association of host haematological and biochemical indices in P.falciparum and P.vivax malaria in order to explore whether these parameters are unique to disease or act as potential diagnostic marker.